Towards the simulation of arbitrarily shaped 3D particles using a homogenised lattice Boltzmann method. (30th August 2018) - Trunk, Robin; Marquardt, Jan; Thäter, Gudrun; Nirschl, Hermann; Krause, Mathias J.
Highlights: HLBM 3D extension for the simulation of real particle suspensions. Holistic automated construction approach for arbitrary-shaped particles from CT scans. Proposed scheme is also applicable for FSI problems. Comparison to classic approaches show excellent accordance of the results. Abstract: The homogenised lattice Boltzmann method (HLBM), previously published by Krause et al. is extended for 3D simulations. The presented approach facilitates the simulation of arbitrarily shaped particles, which are automatically constructed from a geometry file, describing the surface. The proposed method relies on a discrete representation of the particle on a homogeneous grid rather than an approximation by a shape which can be described by a simple analytical equation or a combination of such. Results of numerical experiments are presented, validating the construction of the discrete particle representation, the particle dynamics as well as the acting forces. Moreover, an application of the method for the simulation of limestone particles based on geometry data generated from computer tomography scans is showcased.